"Do what you can with a happy heart": a longitudinal study of patient and family members' lived experiences of physical activity post-myocardial infarction. Issue 14 (3rd July 2022) - Birtwistle, Sarah B.; Jones, Ian; Murphy, Rebecca; Gee, Ivan; Watson, Paula M.
Abstract: Purpose: Physical activity (PA) post-myocardial infarction (MI) can reduce risk of reoccurrence and mortality. Yet uptake of PA through cardiac rehabilitation (CR) is poor, and little is known about the long-term PA behaviour of cardiac patients. This study aimed to explore the lived experiences of patients' engagement with PA post-MI, together with the experiences of their family. Methods: Longitudinal interviews with six family-dyads were conducted which drew on interpretative phenomenology to understand the lived experiences of PA for post-MI patients and family members. Results: Participants described a journey that involved leaving "normality" (doing what PA they wanted and when) and transitioning to a new "normality" (being active within post-MI parameters). This journey was expressed through feelings of "I can't do what I was doing before, " "finding my way, " and "accepting this way". Conclusion: The role of family within the patient's journey was complex, with PA identity, beliefs, and fear of MI re-occurrence influencing PA support both positively and negatively. PA engagement post-MI is a dynamic and interactive process within which the family can have an important influence. IMPLICATIONS FOR REHABILITATION: The process of (re-)engaging in physical activity post-myocardial infarction involves a complex journey towards acceptance of a new "normality". Family play an important role in regulating and supporting patients' physical activity during the rehabilitation process. Promoting positive health beliefs and helping families understand what, how and when patients should be physically active may optimise the rehabilitation journey for post-myocardial infarction patients.